2006
DOI: 10.1021/jp0640777
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers of Disulfide-Functionalized Diacetylenes on Gold Films and Nanoparticles

Abstract: This paper reports on the fabrication of self-assembled monolayers containing disulfide-functionalized diacetylenes. To this purpose, two diacetylene derivatives were synthesized:  the novel 14-(9H-9-carbazolyl)tetradeca-10,12-diyn-1-yl disulfide (CDS9) and the henicosa-10,12-diyn-1-yl disulfide (DS9). Both monomers were employed to prepare two-dimensional self-assembled monolayers (2D-SAMs) by chemisorption on gold-sputtered platforms and three-dimensional self-assembled monolayers (3D-SAMs) on gold nanoclust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 38 publications
(82 reference statements)
2
30
0
Order By: Relevance
“…The signal at 702 cm −1 is attributable to the CCC in-plane bending mode. [31,32] By increasing the irradiation time, the 2092 and 1460 cm −1 components disappear in favour of the 2120 and 1512 cm −1 signals of the red form. The time evolution of the Raman spectra behaves in the whole similarly to that of the electronic spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The signal at 702 cm −1 is attributable to the CCC in-plane bending mode. [31,32] By increasing the irradiation time, the 2092 and 1460 cm −1 components disappear in favour of the 2120 and 1512 cm −1 signals of the red form. The time evolution of the Raman spectra behaves in the whole similarly to that of the electronic spectra.…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectra obtained from the polymerized nanohybrids after deposition onto KBr pellets confirmed the insight that only the lessconjugated red conformation is present in nanoparticles of diameter below 2 nm. 3 ) -a Mode assignment nomenclature: n a = asymmetric stretching, n s = symmetric stretching, d a = asymmetric bending, d s = symmetric bending, d = bending. The peak positions are reported with an error of AE1 cm À1 .…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis conditions were properly manipulated in order to obtain nanoparticles of different core size [3].…”
Section: Synthesis Of Ds9-capped Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the morphology of the metal surface is a key factor both for the achievement of polymerization and for the predominance of one or another polymeric form. This effect was studied in detail by chemisorption of thiol-functionalized diacetylene molecules either on planar metal surfaces having different roughness [3] and on gold nanoparticles [4]. In the second case, it was found that the particle diameter drives the polymerization process and the blue form prevails in the case of larger metal cores.…”
Section: Polydiacetylene-coated Metalsmentioning
confidence: 99%